2009
DOI: 10.1007/978-3-642-05031-2_19
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Large TTCN-3 Projects

Abstract: Experience has shown that the Testing and Test Control Notation version 3 (TTCN-3) language provides very good concepts for adequate test specification, but it was not presented yet how large test systems written in TTCN-3 are structured. This paper presents my efforts to analyze the structure of TTCN-3 projects, to see if such problems manifest, and if possible to provide methods that can detect these problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We have previously defined ( [29]) several code smells for test systems written in TTCN-3 and have shown ( [28]) that publicly available TTCN-3 test systems have room for improvement. We have also already shown ( [26]), that test systems written in TTCN-3, can become large and complex structures. In this article we studied the long term evolution of a large test system in the industry.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We have previously defined ( [29]) several code smells for test systems written in TTCN-3 and have shown ( [28]) that publicly available TTCN-3 test systems have room for improvement. We have also already shown ( [26]), that test systems written in TTCN-3, can become large and complex structures. In this article we studied the long term evolution of a large test system in the industry.…”
Section: Discussionmentioning
confidence: 79%
“…In [26] we have shown that automated test systems written in TTCN-3 can grow large and complex similar to the structures studied in [31]. In [29] we have defined 86 code smells for TTCN-3 and their relations to international software quality standards.…”
Section: Our Contributionsmentioning
confidence: 98%
See 1 more Smart Citation
“…[79,52,21]. Moreover, the scale-free property was justified for large scale test systems as well [115].…”
Section: Scale-free Networkmentioning
confidence: 99%